ANTESEDEN AGRESIVITAS PAJAK PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR: BUKTI DARI NEGARA BERKEMBANG: indonesia - Nurifa Laksmitasari Azizah; Eka Mustikasari (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2024)
The most significant state revenue in Indonesia comes from tax revenues, with a self-assessment system. Based on several previous studies, this system could be a factor in not achieving the tax revenue target. For companies, tax collection is considered a burden that reduces profits; This is what causes companies to carry out tax aggressiveness as a strategy in tax planning. Tax aggressiveness is one of the factors inhibiting state tax revenues. This research aims to analyze the influence of Corporate Governance and Corporate Social Responsibility on tax aggressiveness. The population in this research are property, real estate and construction service sector companies listed on the Indonesian Stock Exchange. The results of this research found that: 1. The Audit Committee has a significant influence on Tax Aggressiveness. 2. Independent Commissioners do not have a significant effect on Tax Aggressiveness. 3. Corporate Social Responsibility has a significant effect on Tax Aggressiveness. 4. The Audit Committee and Independent Commissioner Corporate Social Responsibility together have a significant influence on Tax Aggressiveness.”